Experimental Study on Flow Characteristics of Aeolian Sand in Fractures - Jiarui Chen; Wenhu Gu; Jihua Zhang; Jitao Tang; Zhengzheng Cao; Jingke Wu; Jianxiong Liu; Weizhong He; Fang Shi (Advances in Civil Engineering)
It is one of the important safety problems in the process of mining shallow coal seams in western China that the rock mass affected by mining stress breaks and forms a penetrating fracture, leading to a sand burst in the working face. The self-developed test system is used to carry out the experimental study on the flow characteristics of Aeolian sand in fractures. The research work is focused on the influence of several parameters, such as the thickness of the Aeolian sand layer, the fracture opening, and the fracture dip angle on the velocity of sand particles in fractures. The results show the following: (1) The influence of fracture opening and fracture angle on sand burst rate is much greater than that of sand thickness. No matter what the fracture angle and fracture opening value are, the influence weight of sand thickness on sand burst rate is almost zero. (2) When other conditions are unchanged, with the increase of fracture dip angle, the sand burst rate increases significantly, and the relationship between the sand burst rate and the fracture dip angle is exponential. (3) The influence weight of fracture opening is the largest. With the increase of fracture opening, the sand burst rate increases logarithmically. Finally, according to the test results, the relation equation which can simultaneously describe the influence of fracture opening and fracture inclination on the rate of the sand burst is fitted. This study can provide a theoretical basis and scientific guidance for the prevention and control of coal mine sand inrush disasters caused by roof cracking in western coal mines.